(untitled) (World Science, 2021)
In the event of a burn injury, one of the leading pathogenetic mechanisms of complications is intravascular hemolysis of erythrocytes. Oxidative stress is the initiating factor in the development of hemolysis. The appointment of ceruloplasmin solution is pathogenetically directed at clinical signs of burn shock. Its appointment during a 10-day stay in the clinic is an important component of the intensive care unit. Determining the indices of the functional state and architecture of erythrocytes is an important component of the diagnostic program for burn trauma.